Drug Combinations in Breast Cancer Therapy - Fisusi, Funmilola A.; Akala, Emmanuel O. (Pharmaceutical Nanotechnology, 2019)
Breast cancer therapy involves a multidisciplinary approach comprising surgery, radiotherapy, neoadjuvant and adjuvant therapy. Effective therapy of breast cancer requires maximum therapeutic efficacy, with minimal undesirable effects to ensure a good quality of life for patients. The carefully selected combination of therapeutic interventions provides patients with the opportunity to derive maximum benefit from therapy while minimizing or eliminating recurrence, resistance and toxic effects, as well as ensuring that patients have a good quality of life. This review discusses therapeutic options for breast cancer treatments and various combinations that had been previously exploited. The review will also give an insight into the potential application of the nanotechnology platform for codelivery of therapeutics in breast cancer therapy.
Keywords: metastatic breast cancer